A Review on Regenerative Endodontics - Elham Shadmehr; Nastaran Jenabi Dehkordi (Islamic Dental Association of Iran, 2014)
Background and Aim : Regenerative endodontics with the goal of replacing the lost dental tissues is developing fast. The aim of this study was to review the recent progressions, known limitations and advantages of regenerative treatments compared to other possible treatment modalities .   Materials and Methods : We searched MedLine and PubMed systematically for articles published from May 2000 until May 2013 in English which were relevant to tissue engineering and regenerative procedures using the keywords "cell and tissue based therapy", "regeneration", "stem cell" and "tissue engineering". More valid papers were chosen .   Results : Stem cells, growth factors and an appropriate scaffold are the three essential elements required for tissue regeneration. Revascularization is an ideal regenerative treatment, which uses a fibrin scaffold. This scaffold is made of peri-radicular stem cells, a clot and latent growth factors in dentinal walls. The clinical outcome of revascularization is complete root formation in a premature necrotic permanent tooth. Thus, revascularization is a realistic and worthwhile approach in patients with fair to good prognosis .   Conclusion : Regenerative treatments with the aim of producing a completely formed permanent tooth are going to revolutionize dental science. Regeneration of a fully formed tooth is much more complicated than treatment of an open apex tooth and this issue requires further studies .